خصائص التشريع الجمركي الجزائري - بوحوش، هشام (جامعة الأمير عبد القادر للعلوم الإسلامية, 2020)
يتميز التشريع الجمركي الجزائري بعدة خصائص تميزه عن التشريع الجزائي العام، ويبرز ذلك خصوصا من ناحية اتساع دور السلطة التنفيذية في مجال تحديد محل الجريمة وكذلك ضعف الركن المعنوي في معظم الجرائم الجمركية، بالإضافة إلى الخصوصية من حيث الإثبات (الحجية المطلقة للمحاضر الجمركية)، وكذلك من حيث المسؤولية (بتبنيه فكرة المسؤولية التضامنية) وتقدير الجزاء. إن ما يبرر هذه الخصائص هو السعي لحماية الاقتصاد الوطني وتحقيق موارد إضافية للخزينة العامة.
The Algerian customs Legislation has several characteristics that make it different from the general penal legislation. This is particularly evident in terms of the broad role of the executive authority in determining the place of crime and the weakness of the moral element in most customs crimes, in addition to privacy in terms of proof )absolute authenticity of customs records), as well as responsibility (for adopting the notion of corporate responsibility), Appreciation of penalty . The Justification of these characteristics is to seek to protect the national economy and the achieve additional resources for the public treasury.
Keywords: الجمارك -- القوانين والتشريعات -- القانون الجنائي -- الجزائر